Stridulating Species of Aphids of the Genus Uroleucon (Hemiptera: Aphididae) with Descriptions of a New Species from Iran - Mariusz Kanturski; Shalva Barjadze; Andżela Glumac; Natalia Kaszyca-Taszakowska (Insects)
In this paper, we present a review of stridulating species of aphids of the Macrosiphini genus Uroleucon (Hemiptera, Aphididae) and include 13 species. The most characteristic feature of the reviewed species is the presence of unusual aphids’ peg-like sensilla distributed on the hind tibia, which are rubbed against the surface of the siphunculi. A new aphid species—Uroleucon remaudierei sp. nov., living on Asyneuma persicum and Michauxia laevigata (Campanulaceae) in Iran—is described and illustrated based on the apterous and alate viviparous females. The new species is differentiated from other morphologically similar congeners. An identification key for apterous viviparous females of all Uroleucon species living on Campanulaceae and sound-producing species of the genus Uroleucon are provided. Additionally, a scanning electron microscopy analysis of the apterous and alate viviparous females of this species was made to elucidate the features of the general morphology, antennal sensilla, and stridulatory apparatus for the first time.